2023
DOI: 10.1155/2023/9645789
|View full text |Cite
|
Sign up to set email alerts
|

RRP Regulates Autophagy through the AMPK Pathway to Alleviate the Effect of Cell Senescence on Atherosclerosis

Abstract: Autophagy is closely associated with atherosclerosis and other cardiovascular diseases (CVD). Compound Danshen prescription is widely used as a clinical antiatherosclerotic drug. In our previous studies, we have shown that the combined active component, ginsenoside Rg1-notoginsenoside R1-protocatechualdehyde (RRP), can effectively alleviate endothelial dysfunction and reduce atherosclerotic plaques. However, the association between cellular senescence, caused by reduced autophagy, and atherosclerosis remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…From Han Dynasty (202 BC) to modern Frontiers in Pharmacology frontiersin.org society, DS has been extensively utilized in conjunction with various herbs to address a wide range of health issues, including diabetes, hepatocirrhosis, osteoporosis, and particularly cerebrovascular as well as cardiovascular diseases (Zhang and Ren, 2017). Studies on phytochemistry have revealed that DS contains a variety amount of phenylpropionic acids and diterpenequinones (Liu et al, 2023). Shanzha, commonly considered to be the fruit of Crateagus pinnatifida Bge.…”
Section: Traditional Background Of the Constituent Herbs Of Dsfmentioning
confidence: 99%
See 1 more Smart Citation
“…From Han Dynasty (202 BC) to modern Frontiers in Pharmacology frontiersin.org society, DS has been extensively utilized in conjunction with various herbs to address a wide range of health issues, including diabetes, hepatocirrhosis, osteoporosis, and particularly cerebrovascular as well as cardiovascular diseases (Zhang and Ren, 2017). Studies on phytochemistry have revealed that DS contains a variety amount of phenylpropionic acids and diterpenequinones (Liu et al, 2023). Shanzha, commonly considered to be the fruit of Crateagus pinnatifida Bge.…”
Section: Traditional Background Of the Constituent Herbs Of Dsfmentioning
confidence: 99%
“…DS extracts have been observed to promote autophagy as well as prevent senescence in both human umbilical vein and aortic endothelial cell lines, where it could activate the AMPK signaling and its anti-aging benefits are abolished when AMPKα is suppressed. Also, it has been shown that DS extracts exhibit the activities to trigger autophagy which were exert by LC3 transformations and p62 degradations, decrease the release of pro-inflammatory cytokines in the blood and thus mitigated the degeneration of the aorta in atherosclerosis mouse models, all the actions helped to lower the incidence of atherosclerotic plaques (Ko et al, 2020;Liu et al, 2023). In order to investigate the potential association between Sal B and autophagy as well as apoptosis, Sun et al established a macrophage model of atherosclerosis induced by cholesterol crystals.…”
Section: Anti-apoptosis and Autophagy Promoting Actionsmentioning
confidence: 99%